PENATAUSAHAAN KEUANGAN PADA BENDAHARA PENGELUARAN DI MADRASAH ALIYAH NEGERI (MAN) 5 KABUPATEN AGAM - Fitnawati Fitnawati; Yurismen Efendi (Jurnal Public Administration, Business and Rural Develoment Planning, 2021)
The research was aimed to find out how the treasurer financial administration at MAN 5 Agam Regency, the obstacles faced, and also efforts were made to overcome the obstacles faced. The result of this research find that the financial administration of the spending treasurer at MAN 5 Agam consists of: a) The Expenditure Treasurer records evidence of fund spending transactions into BKU, b) From this recording process in produce documents in the form of a Cash Receipt and Expenditure Book, a VAT / PPh Tax Book, an advance book, an Expenditure Recapitulation Book per Object Details, c) Then the Spending Treasurer makes SPJ the Spending Treasurer consisting of BKU, VAT / PPh Tax Book, and proof of tax payment, Cash Receipts and Expenditures Book, Advance Book, Expenditure Recapitulation Book Per Detail. 2) The obstacles faced include a) SPJ submitted there are still many errors, b) Delays in submitting SPJ, c) Financial reports of MAN 5 Agam are generally still far from expectations. 3) The efforts made include: a) Making improvements and adjustments to the PN and Ph treasurer expenditure tax book reports, b) Increasing the attitude of discipline and responsibility to all human resources, c) Increasing the coordination of cooperation / cooperation for compilers and evaluators of documents. budget documents.